Association of spontaneous abortion and Ureaplasma parvum detected in placental tissue. (2020) - Oliveira, C. N. T.; Oliveira, M. T. S.; Oliveira, H. B. M.; Silva, L. S. C.; Freire, R. S.; Santos Júnior, M. N.; Oliveira, M. V.; Timenetsky, J.; Campos, G. B.; Marques, L. M.
Abstract: Spontaneous abortion is considered a public health problem having several causes, including infections. Among the infectious agents, bacteria of the vaginal microbiota and Ureaplasma parvum have been associated with abortion, but their participation needs to be further elucidated. This study aims to evaluate the influence of Mollicutes on the development of spontaneous abortion. Women who underwent spontaneous abortion and those with normal birth (control) were studied. Samples of cervical mucus (CM) and placental tissue were collected to identify Mollicutes using the quantitative polymerase chain reaction methodology. Eighty-nine women who had a miscarriage and 20 women with normal pregnancies were studied. The presence of Mollicutes in placental tissue increased the chance of developing miscarriage sevenfold. The prevalence of U. parvum in women who experienced spontaneous abortion was 66.3% in placental tissue. A positive association was observed between the detection of U. parvum in samples of placental tissue and abortion. There was a significant increase in microbial load in placental tissue for M. hominis, U. urealyticum and U. parvum compared to the control group. Detection of U. parvum in CM in pregnant women can ascend to the region of the placental tissue and trigger a spontaneous abortion.